Harnessing AI to Improve Operational Effectiveness and Strengthen Organizational Adaptability - Agung Rizky; Ridwan Arifin; Arif Andika; Ora Plane Maria Daeli; Chua Toh Hua (CORISINTA, 2025)
This study explores the dual role of Artificial Intelligence (AI) in improving operational effectiveness and fostering organizational agility, two critical factors for success in today’s dynamic business environment. By leveraging technologies such as machine learning, predictive analytics, and robotic process automation, organizations can streamline workflows, enhance cost efficiency, and enable data-driven decision-making. The research adopts a qualitative approach, analyzing case studies and expert insights to uncover key findings. Results indicate that AI implementation significantly enhances process speed, decision accuracy, and adaptability while reducing operational costs. However, challenges such as resistance to change, high implementation costs, and ethical concerns—particularly regarding data privacy—pose barriers to adoption. To address these, organizations must adopt strategic measures such as phased implementation, robust training programs, and ethical frameworks. The study introduces a conceptual model that illustrates AI's central role in driving efficiency and adaptability, supported by comparative performance metrics demonstrating tangible benefits. This research contributes to the broader understanding of AI’s transformative impact, emphasizing its potential as a catalyst for innovation and competitiveness. Furthermore, it provides practical recommendations for overcoming barriers to adoption, ensuring sustainable integration of AI technologies. By addressing both opportunities and challenges, the findings serve as a roadmap for organizations aiming to harness AI's full potential. Future research should focus on industry-specific applications and strategies to tailor AI adoption to unique organizational needs, thereby maximizing its impact across diverse sectors. This study concludes that AI is indispensable for organizations striving to thrive in a rapidly evolving digital landscape.